Determinantes da taxa de câmbio real brasileira no período 1999-2015: modelo comportamental com crítica pós-Keynesiana e estruturalista - Rafael Galvão de Souza (2016)
The objective of this essay is to study the determinants of the Brazilian real effective exchange rate between January 1999 and July 2015 along with observed misalignments through a behavioral model with permanent and transitory components. The variables (or fundamentals) have been selected searching for a reconciliation of this methodology with the Post-Keynesian literature, especially that developed by John T. Harvey, considering the interaction among real and monetary variables (non-neutrality of money) and the key role in exchange rate determination ascribed to the international financial system, capital flows and expectations formation in a context of fundamental uncertainty. And the results were evaluated using the insights of the structuralist literature, especially that developed by Bresser-Pereira. Our results showed that the exchange rate was undervalued in July 2015, that is, showing a misalignment in which the exchange rate was 14% depreciated in relation to its long term estimated equilibrium. On the other hand, based on the concept of optimal real exchange rate (Nassif et al, 2011), which seeks to establish a reference rate in line with a competitive rate a la Bresser, the exchange rate in July 2015 is found to be rather 12.9% overvalued, pointing to an optimal level of R$/US$ 3,83 at that month.